Fundamentals of cognitive neuroscience a beginner's guide - Gage, Nicole M.; Baars, Bernard (London, United Kingdom San Diego, CA, United States Academic Press is an imprint of Elsevier, 2018)
Fundamentals of Cognitive Neuroscience: A Beginner's Guide, Second Edition, is a comprehensive, yet accessible, beginner{u2019}s guide on cognitive neuroscience. This text takes a distinctive, commonsense approach to help newcomers easily learn the basics of how the brain functions when we learn, act, feel, speak and socialize. This updated edition includes contents and features that are both academically rigorous and engaging, including a step-by-step introduction to the visible brain, colorful brain illustrations, and new chapters on emerging topics in cognition research, including emotion, sleep and disorders of consciousness, and discussions of novel findings that highlight cognitive neuroscience{u2019}s practical applications. Written by two leading experts in the field and thoroughly updated, this book remains an indispensable introduction to the study of cognition.--
1. A framework for mind and brain -- 2. The brain -- 3. Observing the brain -- 4. The art of seeing -- 5. Sound, speech, and music perception -- 6. Language and thought -- 7. Learning and remembering -- 8. Attention and consciousness -- 9. Decisions, goals, and actions -- 10. Humans are social beings -- 11. Feelings -- 12. Sleep and levels of consciousness -- 13. Disorders of consciousness -- 14. Growing Up.
"Elsevier science & technology books"--page facing title page.
Order of authors' names reversed on previous edition.
Includes bibliographical references and index.
Keywords: Cognitive neuroscience; Neurosciences cognitives; Cognitive neuroscience; Cognitive Neuroscience -- methods; Brain -- physiology; Cognition -- physiology